Pengaruh Model Challenge-Based Learning Berbantuan GeoGebra terhadap Kemampuan Berpikir Kritis dalam Menganalisis Informasi Siswa Sekolah Dasar - Nurdiyah Kurniati; Andi Asrafiani Arafah (Bima Journal of Elementary Education, 2025)
The background of this research is based on the urgency of transforming basic education to prepare students to face the challenges of the 21st century digital era. This study aims to examine the effect of the Challenge-Based Learning model assisted by the GeoGebra application on elementary school students' critical thinking skills in analyzing information. The focus of the research lies in strengthening higher-order thinking skills through challenge-based instruction supported by visual technology. The research employed a quasi-experimental method with a one-group pretest-posttest design, without a control group. The sample consisted of 25 fifth-grade students from a public elementary school in Samarinda, selected using purposive sampling. The research subjects were students who received mathematics instruction through a challenge-based approach integrated with digital exploration via GeoGebra. The instrument used was an essay test developed based on indicators of critical thinking skills in mathematical contexts. Data were analyzed using descriptive and inferential statistics, with a paired sample t-test applied to assess the score differences before and after the intervention. The results revealed a significant improvement in students' critical thinking abilities, with posttest scores consistently higher than pretest scores. Inferential analysis yielded a significance value that confirmed a meaningful difference as a result of the treatment. The study concludes that the application of the Challenge-Based Learning model supported by GeoGebra is effective in fostering students’ analytical and critical reasoning skills. Further research is recommended to investigate the model’s effectiveness in other subjects, educational levels, or over a longer duration to broaden its impact in educational practice